Um Estado novo-desenvolvimentista na América Latina? - Bresser-Pereira, Luiz Carlos (2012)
Latin America was probably the region that suffered most in the neoliberal years, because it was also the region where the respective reforms and policies were taken the furthest. For this reason, it was also the region where the neoliberal years first came to an end. In the late 1990s, left wing and economic nationalist political leaders started winning elections. However, a new economic school of thought based on a new concept of structuralist development macroeconomics has been under discussion, and the Ten Theses on New Developmentalism are today an alternative to the Washington Consensus. Does this mean that the developmentalist state has returned? It is too soon to say, not only because ideas and politics seldom match, but also because the rise in commodity prices is threatening industrialization in the region.